Pengaruh Model Numbered Heads Together (NHT) terhadap Hasil Belajar Pendidikan Agama Islam SDN 34 Baringin Singgalang Kecamatan X Koto Kabupaten Tanah Datar - Selfia, Widya; Rahman, Rini (Lembaga Yasin AlSys, 2023)
This study aims to determine the effect of using the Numbered Heads Together (NHT) method on the learning outcomes of fifth grade students at SDN 34 Baringin Singgalang in PAI learning. The type of research is Pre-Experimental Design, namely the One-Group Pretest-Posttest design section. The population in this study were all fifth grade students at SDN 34 Baringin Singgalang as many as 24 students. The samples used in this study were all of class V. The sampling technique was non-probability sampling, this technique consisted of various techniques including saturated sampling. The research instrument used multiple choice test items, which totaled 30 items. The collected data is processed using descriptive statistical analysis, normality test, homogeneity test, hypothesis testing with the help of the SPSS 16.0 application for windows. Based on the output results of SPSS 16 on the hypothesis test using the Paired sample t test which was carried out on student learning outcomes data showed higher posttest results. This result is proven.